Good hair [videorecording (DVD)] - Stilson, Jeff; Rock, Chris (Lionsgate, 2010)
Comedian Chris Rock tackles the very personal issue of hair, and how attaining good hair can impact African American's activities, relationships, wallets, and a self-esteem. Engages in frank, funny conversations with haircare professionals, beautyshop and barbershop patrons, as well as featuring interviews with Dr. Maya Angelou, Nia Long, Ice-T, Raven Symone, and more.